Esophageal Mucosal Autograft for Preventing Stricture After Widespread Endoscopic Submucosal Dissection of Superficial Esophageal Lesions - Zhang, Yu; Mao, Xin-Li; Zhu, Wei; Zheng, Hai-Hong; Zhou, Shen-Kang; Ye, Li-Ping; Li, You-Ming (Turkish Journal of Gastroenterology, 2022)
Background: Although esophageal mucosal autograft prevents esophageal stricture after widespread endoscopic submucosal dissection and has been reported as a new technique, it is relatively unproven in clinical practice. This prospective study was conducted toevaluate our experience using esophageal mucosal autograft to prevent strictures after widespread endoscopic submucosal dissectionin patients with widespread superficial esophageal lesions.Methods: Between October 2017 and June 2018, 15 patients with widespread superficial esophageal lesions were consecutively treatedwith widespread endoscopic submucosal dissection and then underwent esophageal mucosal autograft. The main outcomes measuredincluded esophageal epithelialization and esophageal stricture.Results: The median longitudinal diameter of the widespread superficial esophageal lesions was 5.2 cm. All 15 patients were successfully treated with widespread endoscopic submucosal dissection and esophageal mucosal autograft, and the median procedural timewas 182 minutes. During follow-up (median, 23 months), esophageal epithelialization was found in 13 patients (86.7%), and 7 patientsexperienced esophageal stricture (46.7%). In those 7 patients, the esophageal strictures were successfully relieved after endoscopic balloon dilation or endoscopic radial incision. No complications related to endoscopic balloon dilation/endoscopic radial incision occurred.Additionally, local recurrence was found in 1 patient with poorly differentiated squamous cell carcinoma, and further surgical resectionwas performed.Conclusions: Esophageal mucosal autograft appears to be an efficient approach to reconstructing local esophageal epithelium andmight have a potential role in preventing esophageal stricture after widespread endoscopic submucosal dissection. However, as a newtechnique, it needs more improvement to enhance its role in preventing esophageal stricture after widespread endoscopic submucosaldissection